FtsK translocation on DNA stops at XerCD-dif. - Graham, J; Sivanathan, V; Sherratt, D; Arciszewska, L (Oxford University Press, 2010)
Escherichia coli FtsK is a powerful, fast, double-stranded DNA translocase, which can strip proteins from DNA. FtsK acts in the late stages of chromosome segregation by facilitating sister chromosome unlinking at the division septum. KOPS-guided DNA translocation directs FtsK towards dif, located within the replication terminus region, ter, where FtsK activates XerCD site-specific recombination. Here we show that FtsK translocation stops specifically at XerCD-dif, thereby preventing removal of XerCD from dif and allowing activation of chromosome unlinking by recombination. Stoppage of translocation at XerCD-dif is accompanied by a reduction in FtsK ATPase and is not associated with FtsK dissociation from DNA. Specific stoppage at recombinase-DNA complexes does not require the FtsKgamma regulatory subdomain, which interacts with XerD, and is not dependent on either recombinase-mediated DNA cleavage activity, or the formation of synaptic complexes.